(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
The development of e-Learning is very promising at all levels of education. Universiti Sultan Zainal Abidin (UniSZA) has developed an e-learning or known as Kelip in 2006. However, the impact of e-learning on student achievement has no further explanation. Thus this quantitative study is aimed at exploring whether the use of e-learning, also known as KeLiP at the University of Sultan Zainal Abidin (UniSZA), is able to improve student’s achievement among the excellent students of language (PCB) and the below-average students of language (PKCB). The comparisons between the achievements of both groups are also studied. This experimental study involved 69 UniSZA diploma students taking the Arabic Language Proficiency course level 2 (UBA 1022). The students have been learning through KeLiP for 10 weeks with content materials from the UBA 1022 module which were presented electronically in the form of graphics, images, sounds, videos and hyperlinks. Pre and post test was conducted to evaluate student achievement. The study shows that the use of KeLiP has improved PCB and PKCB achievements with a mean of 26.545 per cent. The excellent students’ performances (PCB) continue to maintain their excellence over PKCB with a mean difference of 11.72 per cent. This study proves that KeLiP is able to improve student’s achievement overall and thus serves as an encouragement for the wide use of KeLiP among students and lecturers.